Investigasi Serangan Backdoor Remote Access Trojan (RAT) Terhadap Smartphone - M. Alvian H Nasution; Agung Tri Laksono (JURIKOM (Jurnal Riset Komputer), 2020)
The Smartphone is one of the needs for everyone at this time, especially in terms of communication with others, but with the development of technology that is also increasingly sophisticated, sometimes we as users do not know there are crimes or attacks that can occur to our smartphone and threaten personal information or data self that is in it, especially android users, where on Android devices can be inserted a malware with the type of RAT or often we call the Remote Access Trojan which is deliberately made using ngrok tools, where the RAT can be made using various file extensions such as. jpg,. MP4, or .apk as was done and will be discussed in this journal. In this journal, an experiment will also be carried out planting RATs on a target, namely an android smartphone which will finally get full access from the smartphone to get full access to any directory that exists shortly after the installation of the RAT hidden in the .apk form file, besides that with this test it is expected that smartphone users, especially Android users, do not root privately, because by rooting the device can open a security hole of the device that we are using and it will be easier to attack from irresponsible parties